Effects of Flavor Dependence on Weak Decays of - Rohit Dhir; R. C. Verma; Avinash Sharma (Advances in High Energy Physics)

(untitled)
We carry out a detailed analysis of effects of flavor dependence of average transverse quark momentum inside a meson on